Quantum-chemical studies on Porphyrins, Fullerenes and Carbon Nanostructures - Loboda, Oleksandr; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book presents theoretical studies of electronic structure, optical and spectroscopic properties of a number of compounds such as porphyrins, fullerenes and heteroatomic single-wall nanotubes. The book presents new, faster calculation methods for application in quantum-chemical theory of electronic structures. It addresses issues of practical importance such as the development of materials for photosensitizers, organic LEDs and solar cells.
Porphyrins -- Exohedral Metallofullerenes -- Nonlinear optical properties of fullerene derivatives -- Enhohedral metallofullerenes -- Fullerene-Porphyrin Dyads -- Linear Scaling Methodology.
Keywords: Chemistry, Physical organic; Nanotechnology; Materials Science; Nanotechnology; Physical Chemistry; Nanoscale Science and Technology